Competitive Electrochemical Immunosensor for Detection of Capsaicinoids in Edible Vegetable Oil Based on Computer Aided Molecular Modeling. Issue 5 (1st May 2022) - Sun, Xia; Zhao, Qingxue; Zha, Chuanyun; Zhang, Jiali; Zhou, Zhongrui; Dong, Haowei; Yang, Qingqing; Guo, Yemin; Zhao, Shancang
Abstract : The adulteration of edible vegetable oil is a serious threat to the health of consumers. Previous studies have shown that capsaicinoids could be used as a marker of adulteration to identify vegetable oils. The key sites of antibody and capsaicinoids were analyzed by computer aided molecular modeling (CAMM), which provided a basis for the selection of modified material and the implanting of antigen and antibody on the electrode in the subsequent construction of the electrochemical immunosensor. Simultaneously, it was determined that the different forces between capsaicinoids and antibody were the important reason for the differences in sensitivity of capsaicinoids. On this basis, combined with the good conductivity and excellent redox characteristic of Fe3 O4 NPs@CeO2, a competitive immunosensor was constructed. Under the optimal conditions, the proposed immunosensor provided a linear range of 10 –3 to 10 4 ng ml −1 with a detection limit of 0.33 pg ml −1 . This study may broaden the interaction between capsaicinoids and antibody, encourage the design of novel performance-enhanced antibody, and provide a new method for the detection of capsaicinoids.